2008
DOI: 10.1111/j.1095-8649.2008.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Monthly indices of the post‐smolt growth of Atlantic salmon from the Drammen River, Norway

Abstract: Indices of the monthly post-smolt growth of three maturity groups of Atlantic salmon Salmo salar from the Drammen River in Norway were examined. Scale samples were collected from 1983 to 2003, providing a retrospective growth history for 2854 individuals. Overall post-smolt growth of all three maturity groups decreased throughout the study period. When the post-smolt year was segmented into 8 monthly indices, there was a significant decline in growth during the fourth and fifth month, typically months of maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 48 publications
(75 reference statements)
2
45
0
Order By: Relevance
“…Similar multi -decadal patterns in post -smolt growth to those reported for the River North Esk were shown for stocks in Ireland (Peyronnet et al 2007), Norway (McCarthy et al 2008 ) and multiple locations across Europe (Friedland et al 2009 ). These higher -resolution data now suggest that the fi rst few summer months at sea defi ne the critical period of growth -mediated post -smolt survival (McCarthy et al 2008 ;Friedland et al 2009 ;Section 16.8 ) and perhaps future analyses of climate impacts should focus on this period.…”
Section: Change In S Ize and G Rowth In The M Arine E Nvironmentmentioning
confidence: 99%
“…Similar multi -decadal patterns in post -smolt growth to those reported for the River North Esk were shown for stocks in Ireland (Peyronnet et al 2007), Norway (McCarthy et al 2008 ) and multiple locations across Europe (Friedland et al 2009 ). These higher -resolution data now suggest that the fi rst few summer months at sea defi ne the critical period of growth -mediated post -smolt survival (McCarthy et al 2008 ;Friedland et al 2009 ;Section 16.8 ) and perhaps future analyses of climate impacts should focus on this period.…”
Section: Change In S Ize and G Rowth In The M Arine E Nvironmentmentioning
confidence: 99%
“…Although a relationship between salmon scale radius size and fish length has been well established in the literature (e.g., Marr 1943;Ricker 1973Ricker , 1976, in common with many other studies (e.g., McCarthy et al 2008;Hogan and Friedland 2010;Marco-Rius et al 2013), scale sizes were not converted to body length or mass estimates, as it would introduce additional errors as a result of (i) scale reabsorption of the final annuli during the final year reducing accuracy (Seo et al 2006) and (ii) uncertainty in the relationship between scale growth to body growth. Scale radius was correlated with fork length (Pearson r = 0.47, p < 0.001; fish length data available from 1998 to 2010).…”
Section: Scale Analysismentioning
confidence: 99%
“…However, the general and continued decline in Atlantic salmon marine survival during the last decades (e.g. Friedland et al, 2003;Jonsson and Jonsson, 2004;McCarthy et al, 2008;Chaput, 2012), suggest observed changes in ocean climate (Hoegh-Guldberg and Bruno, 2010) may be causative.…”
Section: Climate Changementioning
confidence: 99%